Nursing interventions in cases of women victims of domestic violence (Research, Society and Development, 2025)
The present study aimed to analyze nursing practices in the identification and reception of women victims of domestic violence, recognizing the relevance of this care in breaking the cycle of abuse and promoting comprehensive health. It is a literature review with a qualitative and descriptive approach, developed using a total of 9 paper, including articles and books. For the development of the discussion, ten articles published between 2019 and 2025 were selected, with a marked preference for case studies. The chosen databases were: BVS, SciELO, LILACS, and Google Scholar. Based on the selection of studies, it was possible to build a discussion highlighting that nursing practice goes beyond immediate clinical care, involving qualified listening, humanized reception, proper documentation, and safe referral to support and protection networks. It was also possible to identify the persistence of challenges that limit the effectiveness of this care, such as the lack of continuous training, absence of institutional protocols, and work overload. Therefore, this study concluded that investing in professional training and institutional support is essential to ensure ethical, sensitive, and effective care capable of restoring the dignity and autonomy of women assisted.